Perancangan Bilik Laktasi Portabel di Lingkungan Kampus Universitas Madani Yogyakarta : Pengabdian - Maffyra Binar Firstya Mutiara; Dwi Kunto Nurkukuh (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Exclusive breastfeeding during the first six months of a baby's life is crucial for optimal growth and health. However, in higher education environments, women who breastfeed often lack adequate support facilities, such as comfortable and appropriate lactation rooms. Universitas Madani Yogyakarta, as an institution with a significant number of female students and staff, currently does not provide such facilities. This community service activity aims to design a prototype of a portable lactation booth as a practical and flexible solution without requiring permanent renovations. The methods employed include user needs surveys, focused group discussions (FGDs), user-centered design approaches, and three-dimensional model visualization. The outcome is a prototype design of a portable lactation booth that is ergonomic, mobile, and meets standards of comfort and privacy. Although not yet realized in physical form, the design has received positive feedback from potential users and is considered to have strong implementation potential within campus environments. This finding is essential as an initial step toward creating more inclusive and women-friendly educational spaces.